Laparoscopic pyeloplasty for pelvi-ureteric junction obstruction: Our single center experience - Joshi, Robin (Journal of Kathmandu Medical College, 2020)
Background: Open pyeloplasty is considered as the gold standard for the treatment of pelvi-ureteric junction obstruction. Laparoscopic pyeloplasty has added advantages with equivalent success rate and low complication rate. Objectives: The aim is to study our experiences in laparoscopic retroperitoneal and transperitoneal pyeloplasty. Methodology: Sixty-five patients with pelvi-ureteric junction obstruction were included in the study. The study was conducted between October 2016 and May 2019 at Kathmandu Medical College Teaching Hospital. Pelvi-ureteric junction obstruction was evaluated by ultrasound and intravenous or computed tomography urography. Clinical history, hospital stay, complications, success rate and functional outcome were analyzed. Statistical analysis was done using the Statistical Package for the Social Sciences,version 20.0 (SPSS Inc., Chicago, IL, USA). A p-value < 0.05 was taken as significant. Followup of the patients was carried out for six to twelve months clinically and radiologically. Results: Laparoscopic transperitoneal pyeloplasty was performed in 27 males and 8 females. Retroperitoneal pyeloplasty was performed in 30 cases (20 males and 10 females). The mean age was 20.26 ± 3.92 years for all cases. Operative time was longer in retroperitoneal group. There were four conversions in retroperitoneal group. Mean hospital stay was longer in retroperitoneal group with significant p-value<0.001. Success rate was almost similar in both groups with insignificant p-value of 0.46. Conclusion: Transperitoneal laparoscopic pyeloplasty group achieved better results than retroperitoneal pyeloplasty group in terms of hospital stay, complication and drain placement but with almost similar success rate.